The relationship between body image and nutritional status in adolescent girls - Rismawati; Fidelia Angelina Lebang (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background:Nutritional problems in adolescents have serious impacts on the health of young people, impacting the welfare of current and future generations, and affecting the economy and health of the country. Nutritional problems that arise in adolescents are influenced by various factors, one of which is eating behavior and perceptions about body image will affect the nutritional status of adolescents. Purpose: To determine the relationship between body image and nutritional status in adolescent girls. Method: The research method used a quantitative method with a cross-sectional study approach. The sample in this study were female students of Elim High School Makassar who were obtained using a simple random sampling method. The statistical test used was the chi-square test. Results: Based on the results of the Chi-square analysis, the p value = 0.002 was obtained, which means Ha was accepted. Conclusion: Thus, there is a relationship between body image and nutritional status in adolescents